A catenin-dependent balance between N-cadherin and E-cadherin controls neuroectodermal cell fate choices. (August 2018) - Rogers, Crystal D.; Sorrells, Lisa K.; Bronner, Marianne E.
Abstract: Characterizing endogenous protein expression, interaction and function, this study identifies in vivo interactions and competitive balance between N-cadherin and E-cadherin in developing avian ( Gallus gallus ) neural and neural crest cells. Numerous cadherin proteins, including neural cadherin (Ncad) and epithelial cadherin (Ecad), are expressed in the developing neural plate as well as in neural crest cells as they delaminate from the newly closed neural tube. To clarify independent or coordinate function during development, we examined their expression in the cranial region. The results revealed surprising overlap and distinct localization of Ecad and Ncad in the neural tube. Using a proximity ligation assay and co-immunoprecipitation, we found that Ncad and Ecad formed heterotypic complexes in the developing neural tube, and that modulation of Ncad levels led to reciprocal gain or reduction of Ecad protein, which then alters ectodermal cell fate. Here, we demonstrate that the balance of Ecad and Ncad is dependent upon the availability of β-catenin proteins, and that alteration of either classical cadherin modifies the proportions of the neural crest and neuroectodermal cells that are specified. Graphical abstract: Highlights: N-cadherin and E-Cadherin proteins have overlapping and distinct localization. N-cadherin and E-cadherin interact heterotypically. Type I cadherins compete for β-catenin and space on the cell membrane. Alterations in N-cadherin levels lead to reciprocal changes in E-cadherin. Changing type I cadherin levels alters ectodermal derivative specification.